(untitled) (Research, Society and Development, 2022)
The animal production system must be ecologically and environmentally sound in order to provide sustainability, combining new technologies responding to global challenges: climate change and bioenergy among others. This study reports the contribution of technological innovations in the management of pasture and grazing facing the prospect of climate change. A systematic literature review was carried out through the Capes journal portal and the Virtual Library of Agrarian Sciences, using advanced research with the combination of the descriptors “grazing technology”, “pasture management”, “grazing systems”. Impacts of agricultural activities, emission and carbon gas sequestration, the animal’s diet, digesters, integrated systems, greenhouse, livestock and social responsibility through the use of technological innovations and challenges in crop-livestock integration are also discussed. Therefore, the productivity and sustainability must be the foundation for the development of agricultural activity, where scientific and technological knowledge will play a prominent role. Sustainability should be the basis for the economic development of agriculture by increasing productivity, which will reduce the pressure on deforestation.